Salt and pure sodium chloride (MENA Report, 2013)
Supplying flux material (caking sodium chloride) with pneumatic discharge and transport silo tank with maximum moisture of 0.5%. Agency : Departamento de Obras Publicas, Urbanismo, Vivienda y Transportes del Gobierno de Aragon (c) 2013 Al Bawaba (Albawaba.com)